2018
DOI: 10.1016/j.bpj.2018.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Tight Binding through Fuzzy Interactions

Abstract: Many intrinsically disordered proteins (IDPs) form fuzzy complexes upon binding to their targets. Although many IDPs are weakly bound in fuzzy complexes, some IDPs form high-affinity complexes. One example is the nonstructural protein 1 (NS1) of the 1918 Spanish influenza A virus, which hijacks cellular CRKII through the strong binding affinity (K ∼10 nM) of its proline-rich motif (PRM) to the N-terminal Src-homology 3 domain of CRKII. However, its molecular mechanism remains elusive. Here, we examine the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…Moreover, Wu et al identified that the electron density of the C-terminal region of a PRM peptide is missing in the crystal structure of its complex with nSH3 CRK [48], indicating high conformational flexibility of the region. In line with these findings, our previous studies indicated that a fuzzy electrostatic interaction between the structurally dynamic PRM 1918 peptide and the isolated nSH3 CRK domain drives high affinity binding [31,39]. The fuzzy electrostatic interaction Figure 5.…”
Section: Molecular Basis Of the High Affinity Of 1918 Ns1:p85 Complexsupporting
confidence: 72%
See 3 more Smart Citations
“…Moreover, Wu et al identified that the electron density of the C-terminal region of a PRM peptide is missing in the crystal structure of its complex with nSH3 CRK [48], indicating high conformational flexibility of the region. In line with these findings, our previous studies indicated that a fuzzy electrostatic interaction between the structurally dynamic PRM 1918 peptide and the isolated nSH3 CRK domain drives high affinity binding [31,39]. The fuzzy electrostatic interaction Figure 5.…”
Section: Molecular Basis Of the High Affinity Of 1918 Ns1:p85 Complexsupporting
confidence: 72%
“…To test the hypothesis, we measured the KD values between CRK-II and the 1918 NS1 ED-CTT :p85 iSH2 complex in the presence of 1M NaCl. The fuzzy electrostatic interaction, in essence, is a long-range electrostatic interaction mediated by a conformationally flexible ligand [49]; thus, the interaction is screened in a high ionic strength solution [39]. Indeed, we observed that the KD value increased by more than 24-fold in the presence of 1M NaCl (Figure 6B), compared to that in 100 mM NaCl ( Figure 4B).…”
Section: Molecular Basis Of the High Affinity Of 1918 Ns1:p85 Complexmentioning
confidence: 83%
See 2 more Smart Citations
“…[1,4] Deoxyribonuclease and ovalbumin, for example, have identical isoelectricp oints of pI = 5.1, but the formal and measured net charge of both proteins differ by approximately 7u nits at pH 8.4. [4] The systematic absence of experimentally determinedv alues of Z has likely impeded ar igorous understanding of most chemicalp rocesses in which proteinsa re involved including aggregation and self-assembly, [20][21][22][23][24][25][26] ligand binding, [27][28][29][30][31][32][33][34] catalysis, [35][36][37][38][39] electron transfer, [3,6,[40][41][42][43][44][45][46][47] protein crystallization, [14,48] analytical separation, [49,50] and protein engineering. [51][52][53][54][55][56] It is tempting to assume that the formal net chargeo faprotein predicted from generalized residue pK a values (Z seq )issosimilar to the actual net charge that any difference is irrelevant, and the isoelectric point tells us all we need to know about ap rotein's net charge.…”
Section: Introductionmentioning
confidence: 99%